A microsensor‐based method for measuring respiration of individual nematodes. Issue 10 (2nd August 2021) - Maciute, Adele; Holovachov, Oleksandr; Berg, Peter; Glud, Ronnie N.; Broman, Elias; Nascimento, Francisco J. A.; Bonaglia, Stefano
Abstract: Meiofauna (invertebrates that pass through a 1‐mm mesh sieve, but are retained on a 40‐µm mesh) represent the most abundant and diverse animal group on Earth, but empirical evidence of their role in benthic respiration, production and carbon cycling across ecosystems is not well documented. Moreover, how meiofauna respond to changing oxygen conditions is poorly understood. We further developed an incubation system, in which oxygen and temperature conditions are easily controlled and single meiofaunal nematode respiration is resolved in glass capillary tubes, using Clark‐type oxygen microsensor. We performed the respiration measurements after exposing nematodes to different ambient oxygen concentrations, which resulted in 3–60 µM O2 during hypoxic and 80–210 µM O2 during oxic incubations in close proximity to the respective nematodes. Individual nematode respiration rates ranged from 0.02 to 1.30 nmol O2 ind. −1 day −1 and were 27% lower during hypoxic than oxic incubations. Rates derived from established allometric relations were on average fourfold higher than our direct measurements. The presented method is suitable for single nematode respiration measurements and can be adapted to a wide range of experimental conditions. Therefore, it can be used to assess meiofauna contribution to ecosystem processes and investigate species‐specific responses to changing environmental conditions, for example, oxygen stress, increasing water temperature.